2016
DOI: 10.1177/0272431616653474
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization and Related Mental Health Problems in Early Adolescence: The Mediating Role of Parental and Peer Support

Abstract: Peer victimization is a widespread phenomenon especially prevalent in early adolescence. This study investigates the prevalence of peer victimization and its association with mental health problems and impact on everyday life, and the possible mediating effect of parental and peer support. Data are based on a cross-sectional health survey ( N = 9,707) among adolescents (10-13 years) and their parents ( N = 8,210). The Strengths and Difficulties Questionnaire was used to measure mental health problems, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…Thirdly, physical inaccessibility and lack of communication with parents may disrupt parent-child attachment, detrimental to emotional regulation [ 60 ]. We also found that more social support predicted fewer mental health problems, which confirmed previous findings [ 61 , 62 ]. According to the main effect model of social support, social support may directly protect an individual when experiencing stressful events [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…Thirdly, physical inaccessibility and lack of communication with parents may disrupt parent-child attachment, detrimental to emotional regulation [ 60 ]. We also found that more social support predicted fewer mental health problems, which confirmed previous findings [ 61 , 62 ]. According to the main effect model of social support, social support may directly protect an individual when experiencing stressful events [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, positive parenting is associated with decreased levels of psychosocial stress and better self-regulation in adolescents, so they can better cope with stressful situations [ 34 , 35 ]. Furthermore, we count on evidence that a parent–adolescent relationship built on support, communication, and caring renders adolescents less likely to develop problematic behaviors when faced with individual stressful situations, such as peer victimization [ 17 , 36 , 37 ]. Regarding individual protective factors, emotional intelligence in adolescents appears to moderate the negative impact of perceived psychosocial stress [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pada tahun 2014-2015 sebesar 20,8% remaja usia 12-18 tahun (lebih dari 5 juta) melaporkan bahwa mereka telah di buli di sekolah (Lessne & Yanez, 2016). Data lain menunjukkan 17,6% anak laki-laki dan 15,3% anak perempuan dilaporkan menjadi korban bullying (Rasalingam, Clench-Aas, & Raanaas, 2016).…”
Section: Pendahuluanunclassified